2013
DOI: 10.1097/ss.0b013e31829a283f
|View full text |Cite
|
Sign up to set email alerts
|

Cassava Nitrogen Requirements in Thailand and Crop Simulation Model Predictions

Abstract: While cassava is an important crop in diverse regions of Thailand, little information is available to compare sites, select planting dates, and determine nitrogen (N) requirements. In recent years, the Decision Support System for Agrotechnology Transfer (DSSAT) has been used to develop this information. In order to use DSSAT, the cassava model, namely, CSM-CSCRP-Cassava, needs to be calibrated and validated. A cassava response to nitrogen study was conducted in Thailand during the 2011-2012 growing season. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 8 publications
1
9
0
Order By: Relevance
“…Higher N fertilizer rates resulted in higher values for most crop traits in both the 2014/15 and 2015/16 growing seasons, indicating a positive effect of N fertilizer application on crop growth with both linear and quadratic functions. This result is similar to the report from Kaweewong et al (2013 a , b ), who indicated that N fertilizer influences cassava growth in certain production areas in Thailand and that increasing N fertilizer up to 250 kg/ha can increase above-ground biomass and storage root dry weights. Cruz et al (2003) reported that cassava grown under higher N-treatments (12 mM NO 3 – ) had higher photosynthetic capacities and SLA values than cassava grown under lower N-treatments (3 mM NO 3 – ).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Higher N fertilizer rates resulted in higher values for most crop traits in both the 2014/15 and 2015/16 growing seasons, indicating a positive effect of N fertilizer application on crop growth with both linear and quadratic functions. This result is similar to the report from Kaweewong et al (2013 a , b ), who indicated that N fertilizer influences cassava growth in certain production areas in Thailand and that increasing N fertilizer up to 250 kg/ha can increase above-ground biomass and storage root dry weights. Cruz et al (2003) reported that cassava grown under higher N-treatments (12 mM NO 3 – ) had higher photosynthetic capacities and SLA values than cassava grown under lower N-treatments (3 mM NO 3 – ).…”
Section: Discussionsupporting
confidence: 91%
“…However, storage root yield of cassava can be improved by using appropriate production technologies, such as planting with high-yielding cultivars, selecting suitable planting dates and applying adequate fertilizer rates. At present, many improved cassava cultivars are recommended for the production system in Thailand, and each cultivar responds and adapts differently to various management practices (Kaweewong et al 2013 a , b ). Nitrogen (N) fertilizer application is one of the most important management processes for increasing cassava storage root yield.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the dry season, some of the rain‐fed upper paddy fields are normally left fallow without planting for a period of 6–8 months due to a shortage of water resources. The cassava is amenable for growing under upland conditions throughout the year in Thailand (Kaweewong et al., ). It is resistant to drought conditions and can also be harvested from 6 until 24 months after planting, depending on growing conditions (El‐Sharkawy, ; Howeler, ; Howeler et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Parameters for several of the rice cultivars grown in Thailand are provided in DSSAT because rice is an important crop all over the world. Parameters for the cassava cultivars grown in Thailand have been provided in research theses (Matthews and Hunt 1994;Sarawat et al 2000;Kaweewong et al 2013) because cassava is a major crop in Thailand. As we do not currently have parameters for vegetables, the default configuration (i.e., cultivar, dates and amounts of fertilizer and irrigation, and soil type) was used to execute the simulation, because local cultivating data were not available.…”
Section: Crop Modelmentioning
confidence: 99%